Answer:
1. This is a like term
24 = 24
2. This is not a like term
12x - 6 = 46
3. This is not a like term
33 = 5x + 43
4.This is a like term
1 = 1
5. This is not a like term
7x = -48
6. This is a like term
25 = 25
7. This is a like term
60 = 60
8. This is a like term
47 = 47
9.This is a like term
20.6 = 20.6
10.This is a like term
10 = 10
Explanation:
1. 5x + 4x − 6x = 24
5x + 4x = 9x
9x - 6x = 24
3x = 24
We can replace x and turn it into an 8.
3(8) = 24
3 x 8 = 24
24 = 24
This is a like term.
2. 8x + 5 − 4x + 1 = 46
8x + 4x - 5 + 1 = 46
8x + 4x = 12x
12x - 5 + 1 = 46
5 + 1 = 6
12x - 6 = 46
We cannot replace the x with any number to get 46.
So this is not a like term.
3. 33 = 5(x + 8) + 3
5xX= 5x
5 x 8 = 40
33 = 5x + 40 + 3
40 + 3 = 43
33 = 5x + 43
We cannot replace any number with x and get 33.
This is not a like term.
4. 2x + 3(x − 8) = 1
3 x X = 3x
3 x 8 = 24
2x + 3x - 24 = 1
2x + 3x = 5x
5x - 24 = 1
We can replace the x with 5.
5(5) - 24 = 1
5 x 5 = 25
25 - 24 = 1
1 = 1
This is a like term
5. x + x − 2x + 4x = −48
x + x = 1x because x is always a 1
1x - 2x +4x = -48
1x + 2x = 3x
4x + 3x = 7x
7x = -48
We cannot replace x with any number.
This is not a like term.
6. 2(x + 5) + 3x = 25
2 x X = 2x
2 x 5 = 10
2x + 10 + 3x = 25
2x + 3x + 10 = 25
2x + 3x = 5x
5x + 10 = 25
We can replace the x with a 3.
5(3) + 10 = 25
5 x 3 = 15
15 + 10 = 25
25 = 25
This is a like term.
7. 60 = 4(x + 3) + 2(x − 3)
4 x X = 4x
4 x 3 = 12
60 = 4x + 12 + 2(x - 3)
2 x X = 2x
2 x 3 = 6
60 = 4x + 12 + 2x - 6
60 = 4x +2x +12 - 6
4x - 2x = 2x
60 = 2x + 12 - 6
12 - 6 = 6
60 = 2x + 6
We can replace the x with a 33.
60 = 2(33) - 6
2 x 33 = 66
66 - 6 = 60
60 = 60
This is a like term.
8. 47 = 2(x + 3) + 3(x − 3)
2 x X = 2x
2 x 3 = 6
47 = 2x + 6 + 3(x - 3)
3 x X = 3x
3 x 3 = 9
47 = 2x + 6 + 3x - 9
47 = 2x + 3x + 6 - 9
2x + 3x = 5x
47 = 5x + 6 - 9
6 - 9 = -3
47 = 5x + -3
We can replace the x with a 10.
47 = 5(10) + -3
5 x 10 = 50
47 = 50 + -3
50 + -3 = 47
47 = 47
This is a like term.
9. −2(x + 1.4) − 1.8 = 20.6
-2 x X = -2x
-2 x 1.4 = -2.8
-2x + -2.8 - 1.8 = 20.6
-2.8 - 1.8 = -4.6
-2x + -4.6 = 20.6
We can replace x with a 8.
-2(8) + -4.6 = 20.6
-2 x 8 = -16
-16 + -4.6 = 20.6
20.6 = 20.6
This is a like term.
10. 8 − 2(x + 4) = 10
2 x X = 2x
2 x 4 = 8
8 - 2x + 8 = 10
8 - 8 + 2x = 10
8 - 8 = 0
0 + 2x = 10
We can replace x with 5.
0 + 2(5) = 10
2 x 5 = 10
0 + 10 = 10
10 = 10
This is a like term.
I hope this helped. I am sorry if you get this wrong. Have a wonderful day.